Pertimbangan Materialitas Audit: Analisis Profesionalisme, Etika Profesi Serta Pengalaman Auditor - Gracella Theotama; Stevany Arum Rindiani; Shirley Wijaya (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2026)
Materiality level is on of the essential aspects in the audit process because it serves as the basis for auditors in assessing whether misstatement in financial statements may influence the decision making of financial statement users. Therefore, it is necessary to consider the factors that can affect the accuracy of auditors in determining the materiality threshold. This study aims to analyze the influence of professionalism, professional ethics and auditor experience on auditors’ materiality judgments. This study uses primary data obtained through a questionnaire survey. The study population consists of all auditors working at the accounting firms Bharata, Arifin, Munajad and Sayuti, with a sample size of 135 auditors. The data analysis method used is multiple linear regression. The results indicate that professionalism and auditor experience have positive effect on auditors’ materiality judgments, whereas professional ethics have a negative effect on auditors’ materiality judgments. A limitation of this study is that auditors completed the questionnaire during working hours, which may have resulted in less than optimal responses. The findings can serve as and evaluation for Public Accounting Firms, highlighting that enhancing auditors’ professionalism and experience are key factors in producing appropriate materiality judgments.